Michael Toxites y los vocabularios plurilingües de Onomastica (1574) - Núñez, Luis Pablo (El Colegio de México, 2018)
This article analyzes the two vocabularies contained in Onomastica (1574), a work by Michael Toxites (pseudonym of Michael Schütz) not yet considered in Hispanic lexical studies. Similar to botanical works by Caspar Bauhin or Christian Mentzel, Toxites’ Onomastica compiles terms related to mineral and vegetal substances used in Renaissance alchemic and chemical compounds. Divided in two parts, the first ordered by subject, the second alphabetically, the work list common and technical terms in several lan guages (Latin, Hebrew, Arabic, German, French, Spanish, Italian, and English). This study explains the structure of both glossaries, it describes some of the terms included, emphasazing its importance for Spanish language in view of its early datation, and, finally, it tries to establish some of its links to other similar Paracelsian works.